QR Code Learning Media and Elementary Critical Thinking Outcomes: Media Pembelajaran QR Code dan Hasil Pemikiran Kritis pada Tingkat Dasar - Putri, Dinda Angelina; Wati, Tri Linggo (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Critical thinking skills are fundamental competencies in elementary education and require instructional strategies supported by appropriate learning media. Specific Background: The integration of QR Code–based learning media in classroom instruction offers interactive access to digital content and structured problem-solving activities for students. Knowledge Gap: Previous studies have discussed critical thinking and technology integration separately, yet limited research has systematically examined QR Code–based media designed to foster critical thinking indicators at the elementary school level. Aims: This study aims to analyze the implementation of QR Code learning media in improving elementary students’ critical thinking skills. Results: The findings indicate measurable improvement in students’ abilities to analyze problems, evaluate information, and formulate conclusions after participating in learning activities supported by QR Code media. The data demonstrate positive changes across critical thinking indicators observed during the instructional process. Novelty: The study presents a structured design of QR Code–integrated learning media aligned with critical thinking components in elementary education. Implications: These findings provide practical guidance for teachers in integrating digital technology into classroom instruction and contribute to the discourse on technology-supported critical thinking development in primary education. Keywords: Qr Code Learning Media, Critical Thinking Skills, Elementary Education, Digital Learning Integration, Instructional Innovation Key Findings Highlights: Students demonstrated higher analytical performance after structured QR-based activities. Classroom implementation showed consistent progress across evaluation and reasoning indicators. Technology-supported tasks facilitated systematic problem exploration in primary settings.